2020
DOI: 10.1038/s41421-019-0138-2
|View full text |Cite|
|
Sign up to set email alerts
|

“Dysfunctions” induced by Roux-en-Y gastric bypass surgery are concomitant with metabolic improvement independent of weight loss

Abstract: Metabolic surgery has been increasingly recommended for obese diabetic patients, but questions remain as to its molecular mechanism that leads to improved metabolic parameters independently of weight loss from a network viewpoint. We evaluated the role of the Roux limb (RL) in Roux-en-Y gastric bypass (RYGB) surgery in nonobese diabetic rat models. Improvements in metabolic parameters were greater in the long-RL RYGB group. Transcriptome profiles reveal that amelioration of diabetes state following RYGB differ… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
21
0

Year Published

2021
2021
2023
2023

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 20 publications
(22 citation statements)
references
References 43 publications
1
21
0
Order By: Relevance
“…Real-time estimates of are therefore essential for public policy decisions during a pandemic [ 7 , 8 ]. Such estimates can be used to study the effectiveness of non-pharmaceutical interventions (NPIs), or assess what fraction of the population needs to be vaccinated to reach herd immunity [ 9 11 ]. Some social scientists have argued that should be viewed as a fundamental constraint on public policy during the current COVID-19 pandemic [ 12 ].…”
Section: Introductionmentioning
confidence: 99%
“…Real-time estimates of are therefore essential for public policy decisions during a pandemic [ 7 , 8 ]. Such estimates can be used to study the effectiveness of non-pharmaceutical interventions (NPIs), or assess what fraction of the population needs to be vaccinated to reach herd immunity [ 9 11 ]. Some social scientists have argued that should be viewed as a fundamental constraint on public policy during the current COVID-19 pandemic [ 12 ].…”
Section: Introductionmentioning
confidence: 99%
“…To investigate the impact of genetic variants on ACE2 and TMPRSS2 gene expression in various tissues, the GTEx portal was used. As previously described 24 , the ACE2 expression in 20 tissues can be regulated by 15 unique eQTL variants with q-value < 0.05. Further investigation showed that all of these variants except for rs112171234, rs12010448, rs75979613, rs143695310 are shared variants between Iran, China, and the 1000 Genome Project populations with allele frequency > 0.05, which were substantially higher in China and EAS populations (Supplementary File 3 ).…”
Section: Resultsmentioning
confidence: 85%
“…Moreover, 800 Iranian participants in the Iranome project 22 were also utilized. Additionally, 2504 individuals from five populations of the 1000 Genome Project (African, American, East Asian, European, and South Asian) 23 and China population 24 were used.…”
Section: Methodsmentioning
confidence: 99%
“…The classic SEIR model is applied here to simulate the spread of infectious diseases in a population ( Iwata and Miyakoshi, 2020 ; Wang et al, 2020 ). The SEIR model classifies a population into four compartments according to health status, namely (1) susceptible ( S ), those who have not been infected by the disease, (2) exposed ( E ), those who are infected by the disease but are still in latent period without clinical symptoms, (3) infected ( I ), those who have developed clinical symptoms after the latent period, and (4) removed ( R ), those who have recovered or died from the disease.…”
Section: Methodsologymentioning
confidence: 99%